Carl Schmitt w polskich interpretacjach prawniczych 1928–2008 - Święcicki, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The main objective of the paper is to present and discuss the main legal-theoretical interpretations of Schmitt’s thought that were carried out in Poland between 1928 and 2008. Leaving aside political or philosophical perspectives, the author examines one dimension of the reception of Carl Schmitt’s thought in Poland, i.e. the reception developed by legal theorists and historians. Schmitt, a renowned German legal theorist of the 20th century, was known to Polish legal science in the 1920s but his esteem was by far less than Kelsen’s. The fact which deeply influenced the pre-war 1930s and post-war reception of his theories in Poland was his access to the Nazi movement. In the following decades Schmitt was morally condemned as a‘Kronjurist’ of the Third Reich. In the 1990s theorists began to interpret his thought in amore neutral, value-free way.
Keywords: Schmitt, Carl; nauki prawne; Polska; interpretacje; myśl prawna; recepcja